Lifting by levers - Dunn, Andrew (England : wayland, 1991)
Describes simples machines which utilize the principle of levers to move heavy objects, cut material, and make mu
Includes bibliographical references and index.
Keywords: Levers -- Juvenile literature; Lifting and carrying | -- Juvenile literature; Levers; Simple machines